LEGAL SANCTIONS FOR INTELLECTUAL PROPERTY RIGHTS VIOLATIONS IN INDONESIA - Koto, Ismail (Proceeding International Seminar of Islamic Studies, 2023)
Intellectual property rights not only recognize individual intellectual property rights but also the existence of communal intellectual property rights. Recognition of communal intellectual property rights governs intangible cultural heritage through various expressions, representations, practices, skills, knowledge and instruments. They also consider culturally related objects, artefacts, and environments for various groups and communities and in some cases, individuals recognized as part of the cultural heritage. The research method used is normative juridical research, namely legal research conducted by examining literature or secondary data. Submission of claims for copyright infringement can also be carried out criminally. UUHC has formulated actions that are categorized as copyright crimes. Originally, this copyright crime was an offense, but was later changed to a complaint offense under Article 120. By becoming a complaint offense, the action taken is solely based on a complaint from the creator or copyright holder who feels aggrieved, so that law enforcement becomes less effective. disputes that give rise to legal consequences, either because of a violation of positive law rules or because of a conflict with the rights and obligations of a person regulated by positive law provisions.